Porcine model of intracoronary pulverization of stent struts by rotablation atherectomy. Issue 7 (2nd September 2013) - Quang, Thuy Tran; Hatem, Raja; Rousseau, Guy; Dube, Bruno; Samson, Caroline; Schampaert, Erick; Charron, Thierry
<x xml:space="preserve">Abstract</x> Objective To evaluate the feasibility and safety of rotablation atherectomy in a suboptimally expanded stent. Methods Seven pigs underwent suboptimal stent expansion in the left anterior descending coronary. Pulverization of the stent struts was performed by rotablation atherectomy with two different burr sizes. Two types of control porcine models were used: pigs with fully expanded stents and pigs without stents. Continuous electrocardiogram readings as well as microscopic and radiologic analysis of cardiac tissue were performed. Results Rotablation atherectomy reduces the suboptimally expanded stent by (26.95 ± 5.03)%. Ninety‐five percent of the metal microparticles, imbedded in the suboptimally expanded stent group cardiac tissue, are less than 15 μm. Transient vasospasm and ST segments elevations were observed during rotablation atherectomy, which returned to basal conditions at the end of the intervention. Conclusion Our study demonstrated the feasibility and safety of using rotablation atherectomy to pulverize stent struts in a suboptimally expanded stent. © 2012 Wiley Periodicals, Inc.